Changes in phenolic compounds and cellular ultrastructure of arctic and antarctic strains of Zygnema (Zygnematophyceae, Streptophyta) after exposure to experimentally enhanced UV to PAR ratio - Pichrtová, Martina; Remias, Daniel; Lewis, Louise A; Holzinger, Andreas (Microbial ecology, 2013)
Ultraviolet (UV) radiation has become an important stress factor in polar regions due to anthropogenically induced ozone depletion. Although extensive research has been conducted on adaptations of polar organisms to this stress factor, few studies have focused on semi-terrestrial algae so far, in spite of their apparent vulnerability. This study investigates the effect of UV on two semi-terrestrial arctic strains (B, G) and one Antarctic strain (E) of the green alga Zygnema, isolated from Arctic and Antarctic habitats. Isolates of Zygnema were exposed to experimentally enhanced UV A and B (predominant UV A) to photosynthetic active radiation (PAR) ratio. The pigment content, photosynthetic performance and ultrastructure were studied by means of high-performance liquid chromatography (HPLC), chlorophyll a fluorescence and transmission electron microscopy (TEM). In addition, phylogenetic relationships of the investigated strains were characterised using rbcL sequences, which determined that the Antarctic isolate (E) and one of the Arctic isolates (B) were closely related, while G is a distinct lineage. The production of protective phenolic compounds was confirmed in all of the tested strains by HPLC analysis for both controls and UV-exposed samples. Moreover, in strain E, the content of phenolics increased significantly (p = 0.001) after UV treatment. Simultaneously, the maximum quantum yield of photosystem II photochemistry significantly decreased in UV-exposed strains E and G (p < 0.001), showing a clear stress response. The phenolics were most probably stored at the cell periphery in vacuoles and cytoplasmic bodies that appear as electron-dense particles when observed by TEM after high-pressure freeze fixation. While two strains reacted moderately on UV exposure in their ultrastructure, in strain G, damage was found in chloroplasts and mitochondria. Plastidal pigments and xanthophyll cycle pigments were investigated by HPLC analysis; UV A- and UV B-exposed samples had a higher deepoxidation state as controls, particularly evident in strain B. The results indicate that phenolics are involved in UV protection of Zygnema and also revealed different responses to UV stress across the three strains, suggesting that other protection mechanisms may be involved in these organisms.
Keywords: xanthofyly; Phenols; chlorofyl; Arktida; ultrafialové záření; Arctic Regions; fotosystém II (proteinový komplex); Photosystem II Protein Complex; Chromatography, High Pressure Liquid; transmisní elektronová mikroskopie; fenoly; vysokoúčinná kapalinová chromatografie; Antarctic Regions; fotosyntéza; DNA, Plant; Xanthophylls; Streptophyta; Chlorophyll A; Photosynthesis; fylogeneze; Microscopy, Electron, Transmission; DNA rostlinná; chlorofyl a; Chlorophyll; Ultraviolet Rays; Antarktida; Phylogeny